Model Homili dan Maknanya dalam Kehidupan Iman Umat: Studi di Paroki Bunda Hati Kudus Yesus Woloan - Jenner Bernardus Senduk (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2022)
The homily is an integral part of the celebration of the Eucharist that is meaningful to the faith life of the Catholic Church. This research was created to obtain the model and meaning of homily in the Parish of Our Lady of the Sacred Heart of Jesus Woloan. This research aims to trace the passion of the meaning of homily, knowing the ideal model of homily, and the inspiration of homily for the quality of life of the faithful of the people in the Parish of Our Lady of the Sacred Heart of Jesus Woloan. This research uses a qualitative approach with interview, observation, and documentation methods. The informants interviewed were some lay people of Our Lady of the Sacred Heart of Jesus Woloan and the priests who served there. From the results of the study, there are several conclusions: first, the lay people of Our Lady of the Sacred Heart of Jesus Woloan have a clear understanding of homily. Second, lay people and priests have a common understanding of homily. Third, each priest is unique in performing homily. Fourth, the ideal homily model does not attach importance to the duration but the quality of its content. Fifth, homily provides inspiration for the lay people. Sixth, every homily bearer is obliged to equip himself with creativity and good preparation for the sake of a more meaningful preaching for the lay people.